Pelecehan Seksual “Begal Payudara” dalam Perspektif Hukum Pidana Islam: Analisis Putusan 47/PID.SUS/2023/PN BKT - Nur Azizah Syahdia; Busyro Busyro (Lembaga Yasin AlSys, 2026)
The prevalence of sexual harassment cases in the form of “breast grabbing” has caused public anxiety, particularly when criminal verdicts are considered relatively lenient compared with the charges, as reflected in Decision Number 47/Pid.Sus/2023/PN Bkt. This study aims to analyze the judge’s considerations in the decision and examine its conformity from the perspective of Islamic criminal law. This study used field research with a qualitative approach. Primary data were obtained through interviews with judges, while secondary data were derived from court decisions, books, and journals. The data were analyzed descriptively and analytically. The results show that the judge based the decision on the fulfillment of the elements of the criminal act of indecent assault against a child in accordance with statutory provisions, while also considering reconciliation and compensation as mitigating factors. From the perspective of Islamic criminal law, the act corresponds to the concept of jarimah hirabah because it contains elements of violence, terror, and the violation of honor in public spaces. The conclusion of this study emphasizes that although the judge’s decision fulfilled formal juridical aspects, the sanction imposed did not fully reflect the severity of the crime, which has a broad impact on the community’s sense of security from the perspective of Islamic criminal law. The implications of this study indicate the need for evaluation in law enforcement and the strengthening of stricter criminal policies against sexual crimes.